TRANSPARANSI PENGELOLAAN DANA DESA PERSPEKTIF SIYASAH SYARIYYAH (Studi di Desa Bontoala Kecamatan Pallangga Kabupaten Gowa): Studi di Desa Bontoala Kecamatan Pallangga Kabupaten Gowa - Rizky Aulia, Rizka Amalia Mustapa; Rahmiati; Laman, Ilham (Prodi Hukum Tata Negara (Siyasah Syariyyah) Fakultas Syariah dan Hukum UIN Alauddin Makassar, 2025)
This study aims to identify the form and effectiveness of transparency in the management of village funds in Bontoala Village, Pallangga District, Gowa Regency. It employs qualitative field research methods, including observation, interviews, and documentation. The findings reveal that the village government applies transparency through public deliberations and the installation of budget boards. However, this implementation does not fully comply with Article 4 Paragraph 7 of Minister of Home Affairs Regulation No. 13 of 2006, which defines transparency as providing the public with broad access to information. The application of transparency remains ineffective, as many residents are unaware of the budget boards, and community participation in deliberations is low due to the lack of direct communication from village officials. From the perspective of Siyasah Syar’iyyah, transparency is reflected in two core values: Shidiq (honesty in managing and conveying information) and Amanah (delivering information to those entitled to receive it). These shortcomings highlight the need for improved communication and more meaningful openness to ensure community involvement and accountability in village fund management.